2014
DOI: 10.1007/s12200-014-0470-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent progresses on optical arbitrary waveform generation

Abstract: This paper reviews recent progresses on optical arbitrary waveform generation (AWG) techniques, which could be used to break the speed and bandwidth bottlenecks of electronics technologies for waveform generation. The main enabling techniques for optically generating optical and microwave waveforms are introduced and reviewed in this paper, such as wavelength-to-time mapping techniques, space-to-time mapping techniques, temporal pulse shaping (TPS) system, optoelectronics oscillator (OEO), programmable optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 96 publications
0
9
0
1
Order By: Relevance
“…The availability of well-developed techniques for shaping ultrashort light pulses and generating optical arbitrary waveforms [27], [28], [42]- [44] forms the basis for photonicassisted RF-arbitrary waveform generation (RF-AWG).…”
Section: Photonics-assisted Rf-awgmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of well-developed techniques for shaping ultrashort light pulses and generating optical arbitrary waveforms [27], [28], [42]- [44] forms the basis for photonicassisted RF-arbitrary waveform generation (RF-AWG).…”
Section: Photonics-assisted Rf-awgmentioning
confidence: 99%
“…That is, once the CFBG is engineered, the generated waveform cannot be altered and thus, in a sense, RF arbitrariness is sacrificed. However, recent research in this area has shown that by incorporating optically-pumped CFBG structures, a certain amount of RF waveform programmability is attainable [28], [29]. An example of MMW chirp generation with tunable chirp rate and center frequency is reported in [54].…”
Section: (B)mentioning
confidence: 99%
“…(6) in [19], we can obtain that the nonlinear operation regime implies to satisfy the condition σ 0 << δω 2 β 3 L, where σ 0 and δω the RF pulse time duration and the optical source bandwidth, respectively. Equation (2) shows that this approach permits to generate an envelope r(t) completely described in [19] with a proportional dependence on the optical source power distribution modified by a scale factor between the optical frequency ω and the instantaneous angular frequency ω rf =2πf rf …”
Section: System Descriptionmentioning
confidence: 99%
“…Photonic generation of microwave/millimeter-wave signals has been a field of interest in the last years due to its important impact on applications such as radar systems, wireless communications, medical image processing, software defined radio or modern instrumentation where high frequency and large bandwidth signals are required [1,2]. The use of microwave photonics (MWP) technology in microwave signal generation offers new features and improved performance related to the inherent advantages of operating in the optical domain such as low losses, high bandwidth, immunity to electromagnetic interference (EMI) and, especially in this case, also the possibility of tuning and reconfiguration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…La arquitectura de generación basada en conformación temporal de pulsos (Temporal Pulse Shaping, TPS) consiste en la propagación de un pulso ultracorto a través de un par de elementos dispersivos con dispersiones de distinto signo [42,66]. Los elementos dispersivos se sitúan antes y después de un modulador electro-óptico alimentado con una señal eléctrica x(t), como se muestra en la fig.…”
Section: Generación Basada En Conformación Temporal De Pulsosunclassified